2007
DOI: 10.14742/ajet.1262
|View full text |Cite
|
Sign up to set email alerts
|

Factors affecting educational innovation with in class electronic response systems

Abstract: This paper reports the use of Rogers' diffusion of innovation perspective to understand the factors affecting educational innovation decisions, specifically in regard to in class electronic response systems. Despite decreasing costs and four decades of research showing strong student support, academic adoption is limited. Using data collected from academic users, non-adopters and other stakeholders reflecting on factors known to affect innovation diffusion, we find issues of cultural compatibility, complexity … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0
4

Year Published

2007
2007
2020
2020

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 30 publications
(16 citation statements)
references
References 38 publications
0
12
0
4
Order By: Relevance
“…Learning based strategies Attention Students are more focused in class Bergtrom, 2006;Burnstein & Lederman, 2001;Caldwell, 2007;d'Inverno, et al, 2003;Elliott, 2003;Elliott, 2003;Jackson et al, 2005;Jones et al, 2001;Latessa & Mouw, 2005;Siau, Sheng, & Nah, 2006;Slain et al, 2004. Interaction Students interact more with peers to discuss ideas Beatty, 2004;Bergtrom, 2006;Caldwell, 2007;Elliott, 2003;Freeman et al, 2007;Kennedy et al, 2006;Sharma et al, 2005;Siau, Sheng, & Nah, 2006;Slain et al, 2004;Stuart et al, 2004;Trees & Jackson, 2007;Van Dijk et al, 2001.…”
Section: Contingent Teachingmentioning
confidence: 99%
“…Learning based strategies Attention Students are more focused in class Bergtrom, 2006;Burnstein & Lederman, 2001;Caldwell, 2007;d'Inverno, et al, 2003;Elliott, 2003;Elliott, 2003;Jackson et al, 2005;Jones et al, 2001;Latessa & Mouw, 2005;Siau, Sheng, & Nah, 2006;Slain et al, 2004. Interaction Students interact more with peers to discuss ideas Beatty, 2004;Bergtrom, 2006;Caldwell, 2007;Elliott, 2003;Freeman et al, 2007;Kennedy et al, 2006;Sharma et al, 2005;Siau, Sheng, & Nah, 2006;Slain et al, 2004;Stuart et al, 2004;Trees & Jackson, 2007;Van Dijk et al, 2001.…”
Section: Contingent Teachingmentioning
confidence: 99%
“…Technology in the form of a classroom performance system (CPS) was used to gather demographic and quantitative data from the participants. CPS technology is known by many different names such as electronic voting systems (Simpson & Oliver 2007), class electronic response systems (Freeman, Bell, Comerton-Forde, Pickering & Blayney, 2007) or by the nickname 'clickers'. The use of the clickers enabled this data to be collected from the participants quickly, easily and allowed for anonymity.…”
Section: The Deakin University Focus Groupsmentioning
confidence: 99%
“…Although the causes of this recent phenomenon are not readily apparent, many professorsbelieve that it may be an outcome of an exponential growth in digital device usage among students that encourages connectivity in the virtual domain but adversely affects the face-to-face interactions in educational as well as social settings. Recent studies have shown that students' active participation in the learning process, referred to in the literature as active learning, leads to enhanced learning and better student retention [8][9][10][11][12]. Recent developments in technology, coupled with student demographic changes, are beginning to have a disruptive effect on the long standing teacher-centric model for educating engineers.…”
Section: Introductionmentioning
confidence: 99%